2009
DOI: 10.1136/gut.2008.166918
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the region harbouring IL2/IL21 associated with ulcerative colitis

Abstract: Objectives Genetic susceptibility is known to play a large part in the predisposition to the inflammatory bowel diseases (IBD) known as Crohn’s disease (CD) and ulcerative colitis (UC). The IL2/IL21 locus on 4q27 is known to be a common risk locus for inflammatory disease (shown in celiac disease, type 1 diabetes, rheumatoid arthritis, systemic lupus erythematosus and psoriasis), while the roles that IL2 and IL21 play in the immune response also make them attractive candidates for inflammatory bowel disease. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 35 publications
0
110
1
1
Order By: Relevance
“…The confirmation of a CTLA4 variant as an independent risk factor for UC gives further support for a major role of CTLA4 as an inherited risk factor for multiple diseases of immune dysregulation. With an increased incidence of celiac disease in UC patients, and with a genetic link between the two diseases demonstrated in coassociation of IL2 and IL21, 24,25 it is interesting that both celiac disease and UC in our study were associated with the CTLA4 À1661A/G polymorphism. 23 It will be interesting to see whether CTLA4 long (AT)n repeats are similarly associated with celiac disease, and also whether patients concordant for both celiac disease and UC are especially likely to have these CTLA4 risk alleles.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The confirmation of a CTLA4 variant as an independent risk factor for UC gives further support for a major role of CTLA4 as an inherited risk factor for multiple diseases of immune dysregulation. With an increased incidence of celiac disease in UC patients, and with a genetic link between the two diseases demonstrated in coassociation of IL2 and IL21, 24,25 it is interesting that both celiac disease and UC in our study were associated with the CTLA4 À1661A/G polymorphism. 23 It will be interesting to see whether CTLA4 long (AT)n repeats are similarly associated with celiac disease, and also whether patients concordant for both celiac disease and UC are especially likely to have these CTLA4 risk alleles.…”
Section: Discussionmentioning
confidence: 51%
“…[20][21][22] Interestingly, CTLA4 À1722T/C and À1661A/G polymorphisms, both located in the promoter region, were found to be associated with GD 21 and celiac disease, 23 respectively. Celiac disease has been observed more frequently in patients with UC, and genetic connections between celiac disease and UC have also been demonstrated in IL2 and IL21 genes, which are associated with celiac disease in a GWAS; 24 moreover, Festen et al 25 found strong association for these same genes and UC.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence concerning the involvement of a specific variant in this region was not possible due to strong LD in the region. Interestingly, this region has also been shown to associate with type Ⅰ diabetes, rheumatoid arthritis and recently UC, hinting at the presence of a common factor for immune-mediated diseases [115][116][117] . To increase the likelihood of disease-gene identification in this GWAS data, additional non-HLA SNPs were subsequently subjected to genotyping in an even larger replication panel [113,114] .…”
Section: Celiac Diseasementioning
confidence: 99%
“…Importantly, this study also demonstrated that nearly 50% of CD risk SNPs are in close proximity to expression quantitative trait loci (eQTLs), suggesting a likely role for changes in levels of gene expression in CD. As mentioned above, additional GWA studies have identified risk loci shared between CD and other autoimmune conditions such as T1DM, RA, CrD, and ulcerative colitis (UC) (Zhernakova et al 2007(Zhernakova et al , 2011Smyth et al 2008;Barrett et al 2009;Festen et al 2009Festen et al , 2011Cotsapas et al 2011;Gutierrez-Achury et al 2011). These studies have illuminated the tremendously pleiotropic nature of loci underlying autoimmune and other immune related conditions.…”
Section: Presentation Pathophysiology and Genetics Of CDmentioning
confidence: 99%